Laser Engraving for Product Traceability: Advances Toward Sustainable Manufacturing - Lanzilotti, C.O.; Pinto, L.F.R. (Journal of Environmental Accounting and Management, 2026)
Manufacturing systems have embedded the quality control of parts in process, which requires the tracking of components. The development of equipment for marking systems has enhanced the identification of parts in production lines, which increases data reliability. This paper aims to present a laser engraving system implementation in the machining process, in replacing the self-adhesive label for parts identification. The new system consists of the laser engraving machine, database and a programmable logic controller. The case study shows the technical analysis and the economic, environmental and social assessment. The results with fiber laser on the cast iron surface were high contrasts, permanent and speed marking. The investment was US\$64,500.00 and the payback was within thirteen months. The decrease of the risk priority score from 26 to 7 indicated better ergonomic condition. The environmental impact was reduced by the elimination of chemical products.